Bleeding oesophageal varices in a 9 months old infant as a complication of neonatal umbilical catheterization – A case report (Indian Journal of Case Reports, 2020)
Esophageal variceal bleeding following portal hypertension (PHT) is rare in children but associated with significant morbidity and mortality. Neonatal umbilical catheterization is a risk factor for portal vein thrombosis and subsequent development of PHT. We report the case of a 9-month-old male infant that presented with upper gastrointestinal bleeding from esophageal varices. He was delivered at 32 weeks of gestation and had neonatal umbilical catheterization for intravenous fluids and antibiotics administration. Barium meal done after resuscitation revealed esophageal varices. He had a blood transfusion while on admission and was discharged home on oral propranolol. This case report highlights a rare case of bleeding esophageal varices secondary to PHT occurring in an infant who had neonatal umbilical catheterization.